Density Effects on Mixing in Porous Media: Multi-dimensional Flow-Through Experiments and Model-Based Interpretation - Ye, Yu; Liu, Sen; Chiogna, Gabriele; Lu, Chunhui; Rolle, Massimo (Transport in Porous Media, 2025)
Density effects can strongly impact flow, solute transport and mixing processes in porous media. In this study, we systematically investigate and compare variable-density flow and transport in quasi two-dimensional and fully three-dimensional porous media using laboratory flow-through experiments and numerical simulations. Sodium chloride was used as conservative tracer in the experiments, with injected concentrations of 4.8 and 20 g/l, respectively. Average flow velocities of 1, 3, 9 and 27 m/d were selected to represent a wide range of advection-dominated flow conditions (Péclet number 3–100). Numerical simulations were performed to quantitatively interpret the bench-scale experiments, as well as to extend the investigation to a larger domain, allowing the analysis of the impact of a wider range of injected concentrations (0.01–65 g/l) and average flow velocities (0.5–30 m/d). Our results reveal distinct plume patterns, including fingering instabilities, sinking and secondary motion, depending on the density difference, on the average flow velocity and on the dimensionality of the system. The latter plays a key role in causing convective rolls, in the rapid sinking of the injected electrolyte plume, and in preventing the onset of fingering instabilities in the 3-D setups. The outcomes of the flow-through experiments, numerical simulations, and Shannon entropy analysis of mixing enhancement by density gradients illuminate a different mixing behavior, under distinct advection-dominated flow regimes, in quasi 2-D and fully 3-D flow-through systems.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Density effects; Flow-through experiments; Mixing; Porous media; Solute transport